Exercise intensity and technical demands of small-sided soccer games for under-12 and under-14 players: Effect of area per player - Martone, D.; Giacobbe, M.; Capobianco, A.; Imperlini, E.; Mancini, A.; Capasso, M.; Buono, P.; Orrù, S. (The Journal of Strength and Conditioning Research, 2017)
The aim of this study was to evaluate the effects of 6 different areas per player (AP) on exercise intensity (EI) measured during small-sided games (SSGs) and expressed as percentage of maximal heart rate (%MHR) and technical actions (TAs) involvement with the ball, crosses, headers, tackles, shots on goal, dribbling, passing, and target passing-in U-12 and U-14 soccer players during SSGs. Seventeen male U-12 soccer players (age 10.0 ± 0.5 years, body mass 39.3 ± 5.3 kg, and height 143.8 ± 4.6 cm) and 16 male U-14 soccer players (age 13.2 ± 0.3 years, body mass 46.6 ± 11.9 kg, and height 154.8 ± 8.5 cm) performed SSGs with different AP: 40, 50, 66.7, 90, 112.5, and 150 m2. Our results indicate that at larger AP, the U-12 group's mean EI values were significantly higher than those at smaller AP (p = 0.05); in addition, intergroup comparison showed that EI was higher in U-12 than that in U-14 players when AP of 112.5 and 150 m2 were considered (p = 0.05). Technical action analysis evidenced that moving from smaller to larger AP, U-14 players adapted better to AP changes. In conclusion, these results suggest that AP influences differently EI and TAs in U-12 and U-14 players. Our results could be taken into account by conditioning coaches to better tailor the physiological and technical training in young players through the modulation of AP.